Diagnostic Value of Platelet Indices in Predicting Pre-eclampsia - Taweda Khalifa (AlQalam Journal of Medical and Applied Sciences, 2026)
Platelet indices, including platelet count (PC), mean platelet volume (MPV), platelet distribution width (PDW), and plateletcrit (PCT), have been proposed as potential markers for the early prediction of pre-eclampsia. This study aimed to investigate the diagnostic value of PC, MPV, the PC/MPV ratio, and PDW in predicting pre-eclampsia. A prospective cohort study was conducted on 100 pregnant women in their first trimester attending the Obstetric Outpatient Clinic at Al-Bayda Medical Centre for routine care. At each visit, a complete blood count (CBC) was performed to assess platelet indices. The comparison between the pre-eclampsia group (Group I) and the non-pre-eclampsia group (Group II) revealed no significant differences in age or parity (P = 0.426 and 0.812, respectively). However, gestational age was significantly lower in Group I. Hemoglobin levels and total leukocyte counts showed no significant differences between groups. In contrast, PC was significantly decreased in Group I compared to Group II. At a PC ≤214, the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and area under the curve (AUC) for predicting pre-eclampsia were 77.78%, 76.92%, 25.0%, 97.2%, and 0.748, respectively. MPV and PDW were significantly higher in Group I, while the PC/MPV ratio was significantly reduced. In conclusion, platelet indices—including PC, MPV, PC/MPV ratio, and PDW—are significant predictors of pre-eclampsia. These parameters demonstrated marked differences between pre-eclamptic and non-pre-eclamptic women, highlighting their potential utility for early detection and management of pre-eclampsia.